2018
DOI: 10.1111/vde.12675
|View full text |Cite
|
Sign up to set email alerts
|

Use of antipruritic and rehydrating foams on localized lesions of atopic dermatitis in dogs: a small‐scale pilot and comparative double‐blinded study

Abstract: The use of a foam may be useful in cAD to improve both skin lesions and pruritus. Both foams evaluated in this study were equally effective. This method of product delivery is easy to use for owners which is important to improve compliance in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Similar improvement rates were obtained by commonly used drugs (e.g., ciclosporin, prednisolone, oclacitinib), although they were associated with greater side effects [52][53][54][55][56][57][58]. The mean reduction in pruritus observed in this study after fourteen days (42%) was higher than those following the application of two commercially available dermatological mousses tested as monotherapy on eight atopic dogs in a previous study (26% and 33% for Foam A and Foam B, respectively) [59]; however, unlike our study, concomitant medications, including shampoos were not allowed in such a protocol.…”
Section: Discussionsupporting
confidence: 78%
“…Similar improvement rates were obtained by commonly used drugs (e.g., ciclosporin, prednisolone, oclacitinib), although they were associated with greater side effects [52][53][54][55][56][57][58]. The mean reduction in pruritus observed in this study after fourteen days (42%) was higher than those following the application of two commercially available dermatological mousses tested as monotherapy on eight atopic dogs in a previous study (26% and 33% for Foam A and Foam B, respectively) [59]; however, unlike our study, concomitant medications, including shampoos were not allowed in such a protocol.…”
Section: Discussionsupporting
confidence: 78%
“…The application of a mousse is simple through massage, it does not require prior wetting of the skin, nor rinsing or drying afterwards, thus allowing longer direct skin contact and prolonged action [ 30 ]. In recent years, mousse formulations, containing either phytosphingosine and pseudofilaggrin [ 31 ], or plant extracts [ 32 ] have been used in the management of canine atopic dermatitis, in spontaneous cases, improving skin lesions and pruritus. In another study, the authors showed that a mousse containing phytosphingosine and pseudofilaggrin could decrease the skin pH and inflammation in an experimental model of impaired skin barrier [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of topical formulations containing essential fatty acids, with or without ceramides and/or cholesterol plus various additional ingredients, was compared to each other in one RCT 68 and to placebo in four RCTs. 11,[69][70][71] Due to a lack of positive controls, a MS could not be assigned to these formulations.…”
Section: Topical Essential Fatty Acid And/or Ceramide And/or Cholestementioning
confidence: 99%